Measuring the Level of HRIS Governance Capability in the Automotive Financing Company Using COBIT 2019 - Naufal, Muhammad; Sutomo, Rudi (Journal of Information System and Informatics, 2024)
In response to the imperative advancements in information technology, companies strive to leverage it for a competitive edge. An automotive financing entity with over 4,000 employees encounters challenges in governing its Human Resources Information System (HRIS). Difficulties include employee service being negatively impacted by delayed HRIS computations, budgets growing faster than regulations, and branch employees not understanding HRIS. The organization intends to use the COBIT 2019 framework to assess its IT governance to address these issues. Based on qualitative interviews and literature reviews, data collection will identify relevant domain processes—APO03, APO06, APO011, APO07, and DSS06—to address the issues. The research reveals that APO03, APO06, APO011, and APO07 are "Largely Achieved" but with identified gaps, while DSS06 is "Fully Achieved." These findings, derived from audit document analysis, will inform recommendations to address process gaps. The company will be presented with these recommendations to enhance its IT governance and management in alignment with COBIT 2019.